Soft tissue applications of lasers: A review - Bhandari, Rajat; Singla, Kartesh; Sandhu, Simarpreet Virk; Malhotra, Aditya; Kaur, Harmandeep; Pannu, Arshdeep Kaur (International Journal of Dental Research, 2014)
Lasers are widely used in dentistry for various clinical procedures like cavity preparation, surgical procedures, scaling and root planning etc. Since its first use in 1960, lasers are now evolved to be used in all aspects of dentistry. The aim of this review is to describe the application of lasers in oral soft tissue procedures. Soft tissue lasers are becoming popular among the clinicians due to their potential value in surgical procedures providing surface sterilization, dry surgical field and increased patient acceptance. Lasers are effective in ablation of various potentially malignant disorders, obtaining biopsy, periodontal plastic surgeries and providing incisions in surgical conditions.   Keywords: ablation, biopsy, CO2 laser, cyst, fibroma, gingival, periodontal.